2009
DOI: 10.1007/s10661-009-0846-4
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, sources, and exposure profiles of polycyclic aromatic hydrocarbons (PAHs) in particulate matter (PM10) in the north central part of India

Abstract: Airborne particulates (PM(10)) from four different areas within Agra city (a semi-arid region) were collected using respirable dust samplers during the winter season (Nov. 2005-Feb 2006) and were then extracted with methylene chloride using an automated Soxhlet Extraction System (Soxtherm). The extracts were analyzed for 17 target polycyclic aromatic hydrocarbons (PAHs) and the heterocycle carbazole. The average concentration of total PAH (TPAH) ranged from 8.04 to 97.93 ng m(-3). The industrial site had the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…However, being hardly possible to quantify the uncertainties caused by the different methods used, we can only compare the data obtained. The values measured in Veneto appear lower than those reported for the urban Northeast Region of China (Li et al, 2011) and North-central part of India (Masih et al, 2010), but higher than those found in Europe: UK (Delgado-Saborit et al, 2011), Spain (Arruti et al, 2012) and Central Italy (Tuscany: Martellini et al, 2012). In conclusion, even considering the limitations in the use of BaP TEQ approaches summarized in Supplementary material Table 4, the results show particularly worrying conditions for the whole Region, with 17 sites over the threshold value of 1 ng m À3 .…”
Section: Bap Toxic Equivalent Concentrationscontrasting
confidence: 70%
“…However, being hardly possible to quantify the uncertainties caused by the different methods used, we can only compare the data obtained. The values measured in Veneto appear lower than those reported for the urban Northeast Region of China (Li et al, 2011) and North-central part of India (Masih et al, 2010), but higher than those found in Europe: UK (Delgado-Saborit et al, 2011), Spain (Arruti et al, 2012) and Central Italy (Tuscany: Martellini et al, 2012). In conclusion, even considering the limitations in the use of BaP TEQ approaches summarized in Supplementary material Table 4, the results show particularly worrying conditions for the whole Region, with 17 sites over the threshold value of 1 ng m À3 .…”
Section: Bap Toxic Equivalent Concentrationscontrasting
confidence: 70%
“…Table 3 shows a comparison of the derived TEQ values with those observed in previous studies. Although the level in the monsoon season was slightly lower, the average annual TEQ values were markedly higher than those of cities in India (Masih et al, 2010;Cheng et al, 2013) and China (Zhu et al, 2014;Zhou et al, 2005), indicating that the carcinogenic risk of atmospheric PAHs in Kathmandu is extremely high. Furthermore, PAHs are present in the atmosphere in both particle and gas phases.…”
Section: Teq Of Pahsmentioning
confidence: 83%
“…Anthropogenic emissions within the mountain region are not major compared with those in the upwind adjacent regions of South Asia such as the populous, rapidly developing, and highly polluted Indo-Gangetic Plain (IGP), which is a major regional or global source of organic pollutants in the atmosphere (Singh et al, 2013;Zhang and Tao, 2009). For example, Delhi and Kanpur, two large cities in the IGP, exhibited extremely high PAH concentrations, with annual mean values of the sum of several PAHs being 850 and 660 ng/m 3 , respectively (Masih et al, 2010;NEERI, 2006). Asian monsoon circulation and westerly winds distribute and transport anthropogenic and natural air pollutants in the Himalayan region (Ming et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Less attention has been paid on monitoring of Persistent organic pollutants (POPs), especially PAHs that requires more elaborate sampling and analytical protocols. Short term studies in ambient air related to PAHs in particulate phase only have been conducted in this area ignoring the gaseous phase (Rajput et al, 2009;Masih et al, 2010a). Although gas phase PAHs have weaker carcinogenic/mutagenic properties, they are the most abundant in the urban atmosphere and react with other pollutants to form more toxic derivatives (Akyuz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%